Extended-spectrum β-lactamase (ESβL)-producing Escherichia coli in antibiotic-free and conventional chicken meat, Brazil - Fuga, Bruna; Neves, Ingrith; Fontana, Herrison; Bispo, Jessica; Sano, Elder; Cardenas-Arias, Adriana; Esposito, Fernanda; Cardoso, Brenda; Ienne, Susan; Sellera, Fábio P.; Lincopan, Nilton (Frontiers in Microbiology, 2025)
BackgroundContamination of food by antimicrobial-resistant pathogens poses significant risk to consumers and environment, potentially leading to foodborne illnesses, silent colonization, and dissemination of antibiotic-resistant bacteria across geographic borders.MethodsThis study analyzed 32 retail meat samples (12 chicken, 10 beef, and 10 pork) from conventional (CN) and antibiotic-free (AF) production systems in Brazil, assessing WHO bacterial priority pathogens through whole genome sequencing and microbiological methods.ResultsFive broad-spectrum cephalosporin-resistant Escherichia coli strains were isolated from AF chicken meat, including four extended-spectrum β-lactamase (ESβL) producers belonging to sequence types (STs) ST117, ST443, ST1559 and ST3258, and one pAmpC producer carrying the blaCMY-2 gene and belonging to ST57. On the other hand, four E. coli strains resistant to 3rd generation cephalosporins were identified in CN chicken meat, being three ESβL producers of ST38, ST2179 and ST2040, and one pAmpC producer belonging to ST350. Genes conferring resistance to hazardous heavy metals, disinfectants, and pesticides were identified, whereas virulent potential of E. coli ST350 and ST2040 was predicted. Noteworthy, E. coli ST38 was genomically related to lineages previously identified in poultry (North America) and polluted environments (Europe), supporting an intercontinental dissemination within a One Health framework.ConclusionOur findings reinforce the need for continuous surveillance of WHO critical priority pathogens in the chicken meat supply chain from different production systems.